Highly Purified Alloantigen-Specific Tregs From Healthy and Chronic Kidney Disease Patients Can Be Long-Term Expanded, Maintaining a Suppressive Phenotype and Function in the Presence of Inflammatory Cytokines - Cortés-Hernández, Arimelek; Alvarez-Salazar, Evelyn Katy; Arteaga-Cruz, Saúl; Rosas-Cortina, Katya; Linares, Nadyeli; Alberú Gómez, Josefina M.; Soldevila, Gloria (Frontiers in Immunology, 2021)
The adoptive transfer of alloantigen-specific regulatory T cells (allo-Tregs) has been proposed as a therapeutic alternative in kidney transplanted recipients, to the use of lifelong immunosuppressive drugs which cause serious side effects. However, the clinical application of allo-Tregs has been limited due to their low frequency in peripheral blood and the scarce development of efficient protocols to ensure their purity, expansion and stability. Here, we describe a new experimental protocol that allows the long-term expansion of highly purified allospecific nTregs from both healthy controls and chronic kidney disease patients (CKD), which maintain their phenotype and suppressive function under inflammatory conditions. First, we cocultured labelled-CTV Tregs from CKD patients or healthy individuals with allogeneic monocyte-derived dendritic cells in the presence of IL-2 and retinoic acid. Then, proliferating CD4+CD25hiCTV- Tregs (allospecific) were sorted by FACS and polyclonally-expanded with anti-CD3/CD28-coated beads in the presence of TGF-β, IL-2 and rapamycin. After four weeks, allo-Tregs were expanded up to 2,300 times the initial numbers with a purity of >95% (CD4+CD25hiFOXP3+). The resulting allospecific Tregs showed high expression of CTLA-4, LAG-3 and CD39, indicative of a highly suppressive phenotype. Accordingly, expanded alloTregs efficiently suppressed T-cell proliferation in an antigen-specific manner, even in the presence of inflammatory cytokines (IFN-γ, IL-4, IL-6 or TNF-α). Unexpectedly, the long-term expansion resulted in an increased methylation of the Foxp3-TSDR. Interestingly, alloTregs from both normal individuals and CKD patients, maintained their immunosuppressive phenotype and function after being expanded for two additional weeks under an inflammatory microenvironment. Finally, phenotypic and functional evaluation of cryopreserved alloTregs demonstrated the feasibility of long-term storage and supports the potential use of this cellular product for customized Treg-therapy in transplanted patients.